Digitizing English for specific purposes in the era of COVID-19 pandemic - Sugeng Purwanto; Idha Nurhamidah (Master Program in Linguistics, Diponegoro University, 2021)
A critical concern on English for Specific Purposes (ESP) has been voiced to meet the demands for English proficiency to survive in international business exchanges. Not only have most college graduates, majoring in economics and business been challenged by the digital advancement of economics but also the ability to win the tight business competition at international level. This article explored procedures for a syllabus design of English for Specific Purposes (ESP) digitized and functionalized in the sense that it is particularly designed for the online mode of teaching ESP (e-learning) adopting pedagogical applications of Halliday’s Functional Grammar (1994). The digital literacy was much reviewed and discussed for Society 5.0 with the four language skills equally treated within Systemic Functional Linguistics (SFL)’s Language Meta-functions with reference to Cambridge Proficiency Level of English (the CEFR). Recommended herewith is to redesign the ESP syllabus to comply with a high-quality education in the digital age.